2015
DOI: 10.1038/mp.2015.120
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide autozygosity is associated with lower general cognitive ability

Abstract: Inbreeding depression refers to lower fitness among offspring of genetic relatives (1). This reduced fitness is caused by the inheritance of two identical chromosomal segments (autozygosity) across the genome, which may expose the effects of (partially) recessive deleterious mutations. Even among outbred populations, autozygosity can occur to varying degrees due to cryptic relatedness between parents (2). Using dense genome-wide SNP data, we examined the degree to which autozygosity associated with measured co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
50
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(58 citation statements)
references
References 45 publications
7
50
1
Order By: Relevance
“…Here, a validated protocol 28 of increasing popularity has been employed, which could strengthen the reliability of the findings. Another study by Howrigan et al 8 showed, in a sample of 4,854 European-ancestry adults from nine cohorts, that increased ROH burden might be associated with lower intelligence. The main focus on adult participants in both previous studies may limit the comparability of the results, since the genetics of intelligence exhibit largely dynamic patterns over the lifetime 15,16 .…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Here, a validated protocol 28 of increasing popularity has been employed, which could strengthen the reliability of the findings. Another study by Howrigan et al 8 showed, in a sample of 4,854 European-ancestry adults from nine cohorts, that increased ROH burden might be associated with lower intelligence. The main focus on adult participants in both previous studies may limit the comparability of the results, since the genetics of intelligence exhibit largely dynamic patterns over the lifetime 15,16 .…”
Section: Discussionmentioning
confidence: 98%
“…Studies on ROH and cognition in different strata of the general population have shown mixed results, with moderate effect sizes [6][7][8] . While two studies 6,8 suggest that inbreeding depression may decrease adult intelligence, divergent results by Power et al 7 could be explained in view of three evidences. First, assortative mating has recently been highlighted as an important factor underlying psychiatric and behavioral phenotypes [9][10][11][12] , in line with specific findings showing assortative mating in relation to cognitive ability published in the late 20 th century 13,14 genetic effects on brain structure and function, but the evidence of associations between genetic risk for schizophrenia and brain features is scarce, with some studies reporting no overlap between schizophrenia PGRS and subcortical phenotypes derived from magnetic resonance imaging (MRI) 21 ,…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Consanguineous marriages between close relatives as a result of assertive mating 35 is known to cause severe congenital metabolic consequences in the off-spring 1 . In addition to 36 that moderate inbreeding due to isolation in populations has been shown to cause unfavorable 37 outcomes among with cardio-metabolic and neuropsychiatric parameters 2,3 . Inbreeding was 38 shown to associate with an increase in fasting glucose, blood pressure, body mass index 39 (BMI), waist-hip ratio (WHR) and decrease in high-density lipoprotein cholesterol (HDL-C), 40 intelligence quotient (IQ) and height 4,5 .…”
mentioning
confidence: 99%
“…While the association between parental relatedness and monogenic disease risk has been known for more than a century [94], observations with complex and infectious diseases potentially reflect elevated levels of autozygosity as a consequence of prescribed and unintentional inbreeding [95] that enrich individual genomes for deleterious variation carried in homozygous form [96,97]. Indeed, genomic autozygosity levels have been reported to influence a number of complex traits, including height and weight [98][99][100][101], cognitive ability [101][102][103], blood pressure [104][105][106][107][108][109][110][111], and cholesterol levels [111], as well as risk for complex diseases such as cancer [84,85,[112][113][114][115][116], coronary heart disease [84,[117][118][119], amyotrophic lateral sclerosis (ALS) [120], and mental disorders [121,122]. These observations are consistent with the view that variants with individually small effect sizes associated with complex traits and diseases are more likely to be rare than to be common [123][124][125][126], are more likely to be distributed abundantly rather than sparsely across the genome [9,127], and a...…”
Section: Introductionmentioning
confidence: 99%